Content of middle mass molecules and erythrocyte intoxication index in blood while experimental allergic alveolitis under adrenalin myocardial injury and correction of the injury by thiotriazoline - V. B. Pyndus; T. O. Pyndus (Journal of Education, Health and Sport, 2015)
Pyndus Volodymyr, Pyndus Tetyana. Вміст молекул середньої маси і еритроцитарного індексу інтоксикації в крові при експериментальному алергічному альвеоліті в умовах адреналінового пошкодження міокарда та корекція порушень тіотриазоліном = Content of middle mass molecules and erythrocyte intoxication index in blood while experimental allergic alveolitis under adrenalin myocardial injury and correction of the injury by thiotriazoline. Journal of Education, Health and Sport. 2015;5(2):319-325. ISSN 2391-8306. DOI 10.5281/zenodo.17886